Performance of 18F-Fluoride PET or PET/CT for the Detection of Bone Metastases. (February 2015) - Shen, Chen-Tian; Qiu, Zhong-Ling; Han, Ting-Ting; Luo, Quan-Yong
<x xml:space="preserve">Abstract</x> Purpose This study aimed to evaluate the diagnostic accuracy of 18F-fluoride PET or PET/CT compared with 99mTc-MDP bone scintigraphy and 18F-FDG PET/CT in the detection of bone metastases. Patients and Methods An electronic search was conducted using PubMed/MEDLINE and EMBASE. The methodological quality of the included studies was assessed with Quality Assessment of Diagnostic Accuracy Studies 2. All analyses were performed on Stata version 12.0 and Meta-DiSc version 1.4. Results Twenty articles containing 1170 patients were identified. On a patient basis, the pooled sensitivity, specificity, and the area under the summary receiver operating characteristic curve of 18F-fluoride PET or PET/CT were 92% (95% confidence interval [CI], 89%–95%), 93% (95% CI, 91%–95%), and 0.985, respectively. On a lesion basis, the pooled sensitivity, specificity, and area under the summary receiver operating characteristic curve of 18F-fluoride PET or PET/CT were 87% (95% CI, 85%–88%), 95% (95% CI, 94%–96%), and 0.979, respectively. When compared with 99mTc-MDP bone scintigraphy, 18F-fluoride PET or PET/CT showed both higher sensitivity (96% vs. 88%, P = 0.002) and specificity (91% vs. 80%, P = 0.001). When compared with 18F-FDG PET/CT, 18F-fluoride PET/CT showed higher sensitivity (94% vs. 73%, P = 0.003), whereas no significant difference was observed in specificity (88% vs. 98%, P = 0.06). Conclusions 18F-fluoride PET or PET/CT has an excellent diagnostic capacity for the detection of bone metastases and shows advantages when compared with 99mTc-MDP bone scintigraphy and 18F-FDG PET/CT.